KEMAMPUAN MEMBACA CEPAT PESERTA DIDIK KELAS V SD XAVERIUS 2 PALEMBANG - Vincentius Wahyu Dwi Kurniawan (Jurnal PGSD Musi, 2020)
This study aims to determine the level of speed reading ability of 5th grade students of SD Xaverius 2 Palembang. This study uses a mixed methot research method. Using qualitative methods that prioritize the process of occurrence of events in natural situations, while quantitative methods that use mathematical models related to the phenomena that occur. The research subjects in this study were 26 students who took the reading speed test and filled out the reading comprehension test that had been distributed by the homeroom teacher. The data collection technique in this study is to perform a reading speed test which is calculated using a stopwatch and fill out an understanding test in the form of multiple choice. The results of this study are the average ability of all 5th grade students of SD Xaverius 2 Palembang has a medium category with a reading speed of 136kmp. Based on the results of the data on the understanding ability of the 5th graders of SD Xaverius 2 Palembang, it was included in the very good category with an average score of 91. So, based on the data, the 5th graders of SD Xaverius 2 Palembang were classified as very good.